Pranayama Sebagai Praktek dalam Mencegah Virus - I Gusti Made Widya Sena (UHN IGB Sugriwa Denpasar, 2020)
A healthy and ideal body is everyone's dream in the world. Healthy is meant not only physically healthy, but also holistically healthy, which is healthy in the physical body, psychological body as well as in the spiritual body. According to WHO (World Health Organization), healthy is the perfect state of physical, mental, social, not only free from disease or weakness. This indicates that health is not just free from illness and disability, but also has an ideal state of three factors, namely social, psychological and biological factors so that a person can carry out his life activities optimally. So that the body's immunity can work optimally so that the body is not susceptible to disease, then there are a number of things that a person must pay attention to in maintaining and enhancing his body's immunity, including getting enough rest, multiply the consumption of vegetables and fruit, not smoking, avoiding alcoholic beverages, exercising regularly and avoid stress. Pranayama as one of the steps of yoga is a stage carried out by the sadhaka (spiritual seeker) to maintain and enhance the physical and psychological body immunity. This article adopts the author to understand the causes and solutions offered by practicing pranayama to prevent the virus from entering the body. This paper uses a data collection method consisting of observations and documents. The data analysis technique used was qualitative in which his presentation was presented descriptively. The results of this paper are obtained that by doing pranayama, including Nadi Sodhana Pranayama, Kapalbhati Pranayama and Ujjayi Pranayama can calm the dynamic movement of mind waves and form a natural defense shield for the body to prevent the body from various diseases.